Analisis Portofolio Optimum Saham Ditinjau Dari Expected Return Dan Risk Penalty Berdasarkan Model Markowitz Studi Kasus Pada Industri Telekomunikasi - Pardede, Robert Pius; Siallagan, Ernita (STIE Kesatuan, 2007)
Research Target this is the to know influence and analysis from expected return and risk penalty in telecommunications industrial sector. Influence and analysis are conducted to know optimum portofolio. Research that conducted writer is from Industri Telekomunikasi with 3 companies, that is PT. Telekomunikasi Indonesia Tbk, PT. Indosat Tbk, and PT. Infoasia Teknologi Global Tbk. Companies are referred obtained from Indonesia Stock Exchange (IDX). Research Result indicates that Tbk PT Telekomunikasi Indonesia haves expected return highest average in 2005 semester 2 that mean investor conducts invesment on a large scale in referred . Highest Variant in 3003 semester 2 mean reward of level the result in referred. Most lowest Risk penalty owned by in 2007 semester 1 that mean only at in 2007 just risk that accepted investor during account low risk. Unility owned by this company reach maximum satisfaction level in 2005 semester 2. At company PT Indosat Tbk haves highest expected return in 2006 semester 1 and the average of the very top in 2003 semester 1. Highest Variant in 2006 semester 2006 semester 1 that mean level of invesment that conducted investor get a run fors high result in referred. Most lowest Risk penalty owned by this company in 2004 semester 2, this condition shows risk that accounted on investor redah in 2004. Highest Utility in 2006 semester 1 mean with maximum satisfaction for investor. At research result PT Infoasia Teknologi Global Tbk haves expected return the average of highest in 2004 semester 2, this condition shows invesment that continuously conducted by investor. Highest Variant in 2006 semester 1 that mean only at year is referred asset reward from invesment that level. Most lowest Risk penalty owned by in 2003 semester 1 show most lowest risk that experienced by investor. Highest Unility in 2004 semester 2, this condition shows with invesment that conducted reach maximum satisfaction level for a investor